Homo necans - Burkert, Walter, 1931-2015. (Berkeley ; Los Angeles ; London)
xxv, 334 sayfa, [8] sayfa resim
Keywords: “Blood sacrifice, the ritual slaughter of animals, has been basic to religion through history, so that it survives in spiritualized form even in Christianity. How did this violent phenomenon achieve the status of the sacred? This question is examined in Walter Burkert’s famous study.” --